2020
DOI: 10.37934/cfdl.12.9.6075
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Analysis for Solar Panel Subjected with an External Force to Overcome Adhesive Force in Desert Areas

Abstract: The dust accumulation is an undesirable phenomenon in a solar plant environment. The dust removing procedures were using traditional techniques which are led to more loss in power especially in desert areas. Additionally, most of the cleaning techniques are designed according to the concept of vanquishing the adhesive force of dust particles by adding a harmonic excitation force. This force may produce damage to the solar panel. Therefore, the main objective of the current study is to simulate a traditional so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Based on the mesh metric spectrum, a minimum value between 0 and 0.25 is considered excellent for a suitable mesh, while 0.80-0.94 is acceptable. Anything above 1.00 is deemed unacceptable [17]. After the 1.25 mm and 2.5 mm mesh sizes were generated, it was observed that their mesh metric value was 1.25, which exceeded the acceptable threshold of 1 for model analysis.…”
Section: Mesh Sizing Determination Of the Modelmentioning
confidence: 99%
“…Based on the mesh metric spectrum, a minimum value between 0 and 0.25 is considered excellent for a suitable mesh, while 0.80-0.94 is acceptable. Anything above 1.00 is deemed unacceptable [17]. After the 1.25 mm and 2.5 mm mesh sizes were generated, it was observed that their mesh metric value was 1.25, which exceeded the acceptable threshold of 1 for model analysis.…”
Section: Mesh Sizing Determination Of the Modelmentioning
confidence: 99%
“…Producing a mesh that meets the criteria is an acquisition in engineering simulation science that is engineered because computers solve problems based on formulas and various glass and mathematical equations through mesh forms, therefore, the more regular, uniform, and smaller the resulting mesh, the computer will process data with available, but the simulation process that is run also takes a longer time. Both Figures 3 show the average recommended quality of the mesh spectrum according to Ansys experts based on the Skewness and Orthogonal Quality mesh criteria [13].…”
Section: Mesh Qualitymentioning
confidence: 99%
“…In general, the skewness should be below 0.95 and results show that the maximum skewness is very good, and the average skewness is excellent, according to the skewness mesh metric spectrum. [61][62][63] As boundary conditions, while fixed support is attached against translation and rotation at one end of the model, axial force and support against rotation are applied at the other end. The governing equations used in FEA are given in Equations ( 1)-( 10).…”
Section: Finite Element Analysismentioning
confidence: 99%